TAIGA: A Complex of Hybrid Systems of Cooperating Detectors for Gamma Astronomy and Cosmic Ray Physics in the Tunka Valley - Budnev, N. M.; Astapov, I. I.; Gress, T. I.; Grinyuk, A. A.; Grishin, O. G.; Dyachok, A. N.; Zhurov, D. P.; Zagorodnikov, A. V.; Zurbanov, V. L.; Ivanova, A. L.; Kazarina, Yu. A.; Kalmykov, N. N.; et al. (Bulletin of the Russian Academy of Sciences: Physics, 2019)
The relevance and benefits of the new TAIGA gamma observatory complex in the Tunka Valley (50 km from Lake Baikal) are discussed. The main aim of the TAIGA installation is to study high-energy gamma radiation and search for cosmic pevatrons. The first series of gamma stations was commissioned in 2019 and covers an area of 1 km2. Its expected integral gamma radiation sensitivity at an energy of 100 TeV over 300 h of source monitoring is (2–5) × 10−13 TeV cm−2 s−1. It is planned to expand the effective area of TAIGA gamma observation to 10 km2 in the future.